Pemenang Lelang Eksekusi terhadap Jaminan Tanah yang Belum Bersertifikat - Sugianto, M Udik; Amboro, Florianus Yudhi Priyo; Hutauruk, Rufinus Hotmaulana (Pascasarjana Ilmu Hukum, Universitas Widya Gama Malang, 2023)
The large number of people who do not have proof of land ownership is an obstacle in obtaining credit from banks. However, responding to this, the bank allows the bank to be able to accept credit submitted to it. However, it becomes a problem when the auction winner wants to transfer the rights to the land, it cannot be done because the land has not been certified, which results in the auction winner not being able to pay the BPHTB. The research method used is normative legal research. Legal regulations regarding auctions for land that have not been certified are contained in Article 41 Paragraph 4 of the PP on land registration, Articles 76 and 108 of the Regulation of the Minister of Land Registration, Article 34 of PMK Implementation of auctions. Meanwhile, the conflict that occurred was Article 83 of the PMK for the Implementation of the Auction, which required the auction winner to pay BPHTB, while Article 2 of the BPHTB Law states that land that has not been certified does not include land rights. The solution provided by the author is: the head of the land office and the head of the KPKNL provide concessions for BPHTB payments and change the laws and regulations related to allowing uncertified land to be auctioned.